Optimising implementation of European guidelines on cardiovascular disease prevention in clinical practice: what is needed?. (3rd June 2020) - Uchmanowicz, Izabella; Hoes, Arno; Perk, Joep; McKee, Gabrielle; Svavarsdóttir, Margrét Hrönn; Czerwińska-Jelonkiewicz, Katarzyna; Janssen, Arne; Oleksiak, Anna; Dendale, Paul; Graham, Ian M
Abstract: Cardiovascular disease is a model example of a preventable condition for which practice guidelines are particularly important. In 2016, the joint task force created by the European Society of Cardiology (ESC) together with 10 other societies released the new version of the European guidelines on cardiovascular disease prevention. To facilitate the implementation of the ESC guidelines, a dedicated prevention implementation committee has been established within the European Association of Preventive Cardiology. The paper will first explore potential barriers to the guidelines' implementation. It then develops a discussion that seeks to inform the future development of the committee's work, including a new definition of the guidelines' stakeholders (health policy-makers, healthcare professionals and health educators, patient organisations, entrepreneurs and the general public), future activities within four specific areas: strengthening awareness of the guidelines among stakeholders; supporting organisational changes to facilitate the guidelines' implementation; motivating stakeholders to utilise the guidelines; and present ideas on new implementation strategies. Providing multifaceted cooperation between healthcare professionals, healthcare management executives and health policy-makers, the novel approach proposed in this paper should contribute to a wider use of the 2016 ESC guidelines and produce desired effects of less cardiovascular disease morbidity and mortality. Furthermore, the solutions presented within the paper may constitute a benchmark for the implementation of practice guidelines in other medical disciplines.